PENGARUH MEDIA SOSIAL TERHADAP PERILAKU MEROKOK SISWA SMP USIA 12-14 TAHUN DI KOTA SEMARANG - Octavia Rizki Amalia Utari; Aditya Kusumawati; Besar Tirto Husodo (Jurnal Kesehatan Masyarakat (Undip), 2020)
Early adolescents (aged 12-14 years) have vulnerability to the influence of the environment, one of which is the influence of social media. Internet channels and social media are the key marketing strategies of one of the largest cigarette companies in Indonesia, which aims to increase teenage exposure to cigarettes. This study aims to determine the effect of social media on smoking behavior of 12-14 year old junior high school students in Semarang City. This research is descriptive in nature, using quantitative methods through the interview process with a questionnaire instrument and cross sectional approach, with a population of 32,344 students spread across 187 schools. Case sample of 110 students taken using multistage random sampling technique. Data analysis was performed by univariate and bivariate analysis. As many as 42.7% of respondents in this study had smoking behavior. Bivariate test results in this study indicate that the variables of individual attitudes (p = 0.005), social media exposure (p = 0.000) and self efficacy (p = 0.000) have a relationship with smoking behavior of 12-14 year old junior high school students in Semarang City. One factor that causes the influence of social media on smoking behavior is the interest of adolescents in the content of cigarettes so that teens are interested in trying cigarettes. Another factor that influences is the respondent's self efficacy in receiving stimulus from his social media. So that junior high school students aged 12-14 years are expected to be able to have strong self-efficacy and firm attitudes so that they are not easily affected by exposure to social media, especially cigarette-related content.